2018
DOI: 10.5539/jas.v10n4p370
|View full text |Cite
|
Sign up to set email alerts
|

Soil Chemical Attributes under Crop-Livestock-Forest Integration System and in Different Land Uses in Mata dos Cocais Region

Abstract: The sustainability of ecosystems is closely linked with the assessment of soil properties that estimate their quality. This work proposes to evaluate soil chemical attributes as a function of the implantation of a crop-livestock-forest integration system (ICLF) in the region of Mata dos Cocais in the state of Maranhão, Northeast Brazil. The four different land uses evaluated were native vegetation with babassu, capoeira vegetation, degraded pasture and area under ICLF system (with marandu grass, maize and euca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 13 publications
(13 reference statements)
2
3
0
1
Order By: Relevance
“…In this study, use of K fertilizers in soil had minimum effect in altering the soil pH. This is also supported by Reis et al, (2018) who observed that potassium fertilizer levels did not affect soil pH. Although decrease in soil pH with the application of fertilizers was expected, it was not seen in this case of study.…”
Section: Potassium Fertilizers On Soil Reactionsupporting
confidence: 79%
“…In this study, use of K fertilizers in soil had minimum effect in altering the soil pH. This is also supported by Reis et al, (2018) who observed that potassium fertilizer levels did not affect soil pH. Although decrease in soil pH with the application of fertilizers was expected, it was not seen in this case of study.…”
Section: Potassium Fertilizers On Soil Reactionsupporting
confidence: 79%
“…It is worth noting that in these cases variability decreased over the experimental period. According to Reis et al (2018), variations of chemical soil attributes are related to irregular fertilization and liming. Statistically, it can be translated into high heterogeneity around the average for chemical attributes in the assessed area.…”
Section: Resultsmentioning
confidence: 99%
“…This nutrient dynamic is exacerbated by the sandy texture and consequently high macroporosity of Quartzarenic Neosols. However, it can be improved -given the soil's low cohesion between particles and low levels of cementing agents (Reis et al, 2018). In any case, according to the authors, such low levels of Ca and Mg would be sufficient to reach average annual increments of up to 20 m 3 ha -1 year -1 in timber production.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Os teores de K, Ca, Mg e Al apresentaram variabilidade alta, variando entre 33,2 e 79,9%. Segundo REIS et al (2018), as variações dos atributos químicos do solo podem ser causadas por manejos silviculturais irregulares ou alocação de clones não específicos para a área. De maneira geral, é retratada alta heterogeneidade dos atributos químicos nas áreas avaliadas.…”
Section: Variabilidades Dos Teores Dos Atributos Químicos E Físicos Do Solounclassified